1985
DOI: 10.1021/ja00311a003
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectrum, structure, and energy of [1.1.1]propellane

Abstract: The structure of [l.l.l]propellane (bond lengths and angles) was determined from an analysis of the rotational components of the infrared bands of the parent compound and of its d6 derivative, and it was found to be in good agreement with the structure calculated including electron correlation. The central C-C bond length was 1.60 ± 0.02 Á which is ~0.09 Á longer than that in cyclopropane. The infrared and Raman spectra were obtained and are in good agreement with the calculated spectrum. A constrained adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
88
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 3 publications
7
88
0
Order By: Relevance
“…1 On the other hand, many arguments derived mainly from spectral studies, including those of classical vibrational spectroscopy, 24,25 low-energy electron impact spectroscopy, 26 photoelectron spectroscopy 27 and electron momentum spectroscopy, 28,29 lead to the conclusion that the bridgehead-bridgehead bond in propellane should be interpreted as an ordinary chemical bond, but with inverted bonding hybrids. In the last study, 29 the complete valence electronic structure of propellane was reported and the resulting wavefunction was determined, which enabled the authors to derive a number of its molecular properties, confirming, in particular, the physical existence of the central bridgehead-bridgehead bond with a 0.70 bond order (very similar to that of 0.73 derived by Wiberg et al 10 ). The strength of this 'bond phantom' was estimated to be ca 60 kcal mol 1 , 30 whereas according to NBO analysis 31 the occupancy of the central bonding orbital is 1.83 and that of the antibonding orbital is 0.15.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…1 On the other hand, many arguments derived mainly from spectral studies, including those of classical vibrational spectroscopy, 24,25 low-energy electron impact spectroscopy, 26 photoelectron spectroscopy 27 and electron momentum spectroscopy, 28,29 lead to the conclusion that the bridgehead-bridgehead bond in propellane should be interpreted as an ordinary chemical bond, but with inverted bonding hybrids. In the last study, 29 the complete valence electronic structure of propellane was reported and the resulting wavefunction was determined, which enabled the authors to derive a number of its molecular properties, confirming, in particular, the physical existence of the central bridgehead-bridgehead bond with a 0.70 bond order (very similar to that of 0.73 derived by Wiberg et al 10 ). The strength of this 'bond phantom' was estimated to be ca 60 kcal mol 1 , 30 whereas according to NBO analysis 31 the occupancy of the central bonding orbital is 1.83 and that of the antibonding orbital is 0.15.…”
Section: Introductionmentioning
confidence: 52%
“…8 In spite of its remarkable deviation from tetrahedral geometry characterized by inverted carbons at bridgeheads and considerable steric strain of 98 kcal mol 1 (1 kcal D 4.184 kJ), 9 propellane was found to be surprisingly stable. 10 The relatively high chemical stability of propellane was explained 7 by the fact that breaking of the central bridgehead-bridgehead bond releases only less than one-third of its strain energy while breaking of the peripheral carbon-carbon bond is symmetryforbidden. Higher propellanes with enlarged fused rings have also received a good deal of attention and it was a challenging task to apply the second-order polarization propagator approach (SOPPA) 11 to calculate carbon-carbon spin-spin coupling constants, J(C,C), in the series of propellanes 1-6 in continuation of our previous communications dealing with the three-membered rings, symmetries are given in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although of a relatively short distance, the fusion bond in the cyclopropane rings is subject to considerable variation as observed in the X-ray crystal structure of 11 (Sect. 2.2) and could possibly be considered a weaker than normal C-C bond, as had been discussed for [I .I .l]propellane [42]. Actually, the effective bridgehead or fusion C-C single-bond strength in both [l.l.l]propellane as well as in 6-6-closed methanofullerenes seems not to be established.…”
Section: The Different Effects On Physical Properties and Chemical Rementioning
confidence: 96%
“…Surprisingly, there are almost no thermochemical data for any propellane except for reaction calorimetry for the simplest one, the triple cyclopropane [1.1.1] species [90], and the likewise cyclopropane-containing [3.2.1] species [91]. Even more surprisingly, calorimetric data for species with two or more cyclic ester groups (i.e.…”
Section: Introductionmentioning
confidence: 99%